Hierarchical fiducial marker design for pose estimation in large‐scale scenarios. Issue 6 (7th March 2018) - Wang, Hao; Shi, Zongying; Lu, Geng; Zhong, Yisheng
Abstract: In this paper, a hierarchical fiducial marker, called HArCo, is designed to guarantee a smooth pose estimation for large‐scale applications. HArCo markers have a visually identifiable structure on multiple scales, so they can be used for consistent pose estimation across a range of altitudes. Experimental results are presented to validate the performance of the proposed methodologies; oscillating platform landing experiments were conducted to show the ability of HArCo to be used in real landing tasks on the deck of a ship.